KARAKTERISTIK FISIK RUMAH TINGGI SUWAWA DAN RUMAH BELELI TAUDA’A DI PROVINSI GORONTALO - Umar, Umar; Eka, Rahmawati (Universitas Bina Taruna Gorontalo, 2023)
Abstract: Physical Characteristics of the Tall Suwawa House and the Bele Li Tauda'a House in Gorontalo Province. This research aims to identify the physical characteristics of the Suwawa High House and the Bele Li Tauda'a House. The research method uses descriptive qualitative by means of a field survey which aims to explore and obtain facts and factual information about the condition of tall houses in the district. Suwawa district. Bone Bulango and Bale Li Tauda's house are in Kel. Pauwo district. Bone Bulango.. Field survey was carried out at the location in Kab. Bone Bolango and Gorontalo Regency in April – May 2023, starting with initial data collection followed by semi-structured interviews, field observations then structuring the data, as well as confirming the data with the reality in the field and the views of traditional leaders. The results of the research show that (1) that the physical characteristics of both are the same on the roof (2) the top part is triangular in shape with a second layer in the middle of the building roof. The conclusion from the research carried out is that the two buildings are still standing strong even though the buildings are no less than 100 years old because the shape of the facade is not influenced by other materials. The local purity of wood still dominates, which is a material chosen directly by local people and is maintained to this day.